Peran Ganda Perempuan Terhadap Kinerja dan Kualitas Kerja - Naomi Margaretha Hutahaean*; Wibisono Ghany Fitriadi; P. Tommy Y. S. Suyasa (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Education is one of the basics in the current era of globalization, many women are working as workers rather than taking care of the household. In general, a high level of education with adequate access to employment makes women feel comfortable with their lives completing work outside the home. At this time not only husbands have to work to meet the needs of their families, but many wives also work. In this study the authors will reveal the performance of working mothers who will be influenced by dual role conflicts that can be experienced by dual role conflicts that can be experienced by working mothers. With a high intensity of dual role conflict, a working mother contributes to a decrease in her performance because a working mother will experience depression, increased stress, increased physical complaints and low energy levels. The data that has been obtained will be analyzed qualitatively which will be in the form of descriptions rather than numbers.